(3ebGdI aj JHjjf hLhO GdCehQ GdYGejI hGdfMh GdPi Ydjg jchf eMehdkG hGdfMh GdPi jNQL Hg Cf jchf eMehdkGs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3bGd GNJda GdeJadSahf ai GUfGa hLhO GdGehQ GdJi JNJda ef bHd GdcdjI hGdLRFjI s
(3BNQgG (B:s
(3hPdc Gf eYfi cd ehLhO dcd hGMO ai LRFjI ZjQg ddCNQ abO JHjf hLhO GehQ YGejI eMehdI Ydi GcKQ ef hGMO hYdi Gi fMh jUM MedgG hYdi Gi fMh dG jUM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GfXQg eY GdeNWhW Qbe (B302 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(4/4901) s
Keywords: (3GdadSaI hGdefWbs